2019
DOI: 10.21470/1678-9741-2018-0333
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-Term Outcomes of Surgical Treatment of Ebstein’s Anomaly

Abstract: ObjectiveThis study aimed to evaluate Ebstein’s anomaly surgical correction and its early and long-term outcomes.MethodsA retrospective analysis of 62 consecutive patients who underwent surgical repair of Ebstein’s anomaly in our institution from January 2000 to July 2016. The following long-term outcomes were evaluated: survival, reoperations, tricuspid regurgitation, and postoperative right ventricular dysfunction.ResultsValve repair was performed in 46 (74.2%) patients - 12 of them using the Da Silva cone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The cone technique shows more favorable outcomes, especially in the short and long term in the adult age group. Moreover, current data suggest a low percentage of medium-term hospital mortality in the neonatal group in large series 4,5 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The cone technique shows more favorable outcomes, especially in the short and long term in the adult age group. Moreover, current data suggest a low percentage of medium-term hospital mortality in the neonatal group in large series 4,5 .…”
Section: Introductionmentioning
confidence: 60%
“…This technique brings the leaflets of the tricuspid valve to the true ring, making the longitudinal and level plication of the atrialized right ventricle. This approach adds an advantage to the leaflet for its coaptation, and this restores the geometry and function of the right ventricle, thus avoiding the use of a prosthetic ring 4,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results of our hospital as well as other centers reveal that the 10-year survival of Ebstein's anomaly is more than 90%. 5,9,12,13 Many studies have reported the excellence of cone repair, [14][15][16][17][18] however, although it is performed in our institution from 2008, only 30 operations have been performed till date. A total of 5 patients required reoperation after cone repair; however, patients who underwent cone repair from 2014 did not require a reoperation (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Hesitation regarding the surgical treatment for Ebstein's anomaly has mainly been due to recurrent arrhythmia after surgery and the requirement for repetitive surgery. [3][4][5][6] However, with the introduction of the cone reconstruction technique in 2007 by da Silva and colleagues, 7 more anatomic repair has become possible compared with that with the previous Carpentier technique. Ebstein's anomaly repair with Cone reconstruction is being performed in our hospital since 2008, and this study was conducted to determine whether Cone reconstruction results in better clinical outcomes than conventional repair.…”
Section: Introductionmentioning
confidence: 99%
“…Ebstein anomaly's most common symptoms are cyanosis, dyspnea, decreased Arrhythmias are common as well and include accessory conduction pathways (Wolff-Parkinson-White syndrome) in about 15-20% of the defected ones and around 30-40% of those affected patients will develop atrial tachyarrhythmias by age 50 [Khositseth 2004;Stulak 2015]. Other commonly associated cardiac defects include atrial septal defect or patent foramen ovale (70-90%), ventricular septal defect (2-6%), and RV outflow tract obstruction that can occur as a secondary to structural abnormalities (pulmonary valve stenosis or pulmonary atresia), branch pulmonary artery stenosis or patent ductus arteriosus [Brown 2008;Da Silva 2019;Veen 2019]. In cases where pre-excitation is present (Wolff-Parkinson-White syndrome), preoperative electrophysiologic study and ablation usually are recommended at age of 4 to 5 years and typically followed by surgical repair of the anomaly.…”
Section: Introductionmentioning
confidence: 99%